Tulip piercing the aorta: a rare case of IVC filter aortic perforation and obstruction. Issue 10 (29th October 2018) - Desai, Kshitij; Cook, Jason; Brownie, Evan; Zayed, Mohamed
ABSTRACT: Prolonged implantation of inferior vena cava (IVC) filters can lead to significant morbidity. We present a 25-year-old man with antiphospholipid syndrome, lower extremity deep vein thrombosis, and subsequent Gunther-Tulip IVC filter placement. More than 10 years following IVC filter placement he developed progressive abdominal and back pains. Cross-sectional angiography revealed that he had a chronic IVC occlusion, and IVC filter limb extensions into the infrarenal aorta, lumbar spine, and right psoas muscle. The IVC filter limb protruding into the aorta had also pierced through the backwall to lead to partial lumen thrombosis and obstruction. The patient underwent a transabdominal exposure of the infrarenal IVC and aorta, filter explantation and aortic patch angioplasty repair. This case highlights the severity of aortic injury from a protruding IVC filter limb that necessitated open aortic repair. Improved selection, monitoring and retrieval stewardship of IVC filters can help reduce the risk of unintended aortic complications.